Upaya Pemerintah dalam Menurunkan Angka Pernikahan Dini di Desa Teluk Sentosa Kabupaten Labuhan Batu - Azris, Dian Novelia; Mailin, Mailin (UIR Press, 2024)
This study aims to determine the government's efforts to reduce the number of early marriages in Teluk Sentosa Village, the government party referred to here is the religious affairs office (KUA). This research uses a descriptive qualitative method which aims to describe the atmosphere or situation in the research. This research was conducted by means of observation, interviews and documentation conducted with two informants in the form of religious instructors at the religious affairs office. The results found are: that the government has made many efforts to reduce the number of marriages in Teluk Sentosa village, one of which is by means of a socialization program carried out by them and notification of marriage requirements on a regular basis, which is carried out by the KUA government to the community and also adolescents. . In addition, it provides education about early marriage so as to provide new, open views and changes to the community regarding early marriages that occur, especially in Teluk Sentosa village. Religious instructors are presented as an aid in guiding the surrounding community in carrying out efforts made from the religious affairs office itself. In addition, the religious affairs office (KUA) has also provided solutions and also problem solving if things happen that are not desired in the underage couple, then the government has negotiated with certain conditions so that it can make it easier for the couple.